Frequency and characterization of RHD and RHCE variants in the Noir Marron population from French Guiana. Issue 12 (26th October 2022) - Laget, Laurine; Izard, Caroline; Durieux‐Roussel, Elisabeth; Filosa, Lugdivine; Bailly, Pascal; Mazières, Stéphane; Chiaroni, Jacques
Abstract: Background: The RH system is one of the most polymorphic blood group systems due to the proximity and opposite orientation of RHD and RHCE genes. Numerous alleles are described and can affect Rh protein expression. This complexity is especially evident in populations of African origin. We performed RHD and RHCE genotyping of the Noir Marron population in French Guiana. This population belongs to the Maroon community who are direct descendants of African slaves, who escaped from Dutch plantations, in the current day Suriname, during the 17th century. They represent an original ethnic group with highly blended culture. Methods and materials: A total of 89 DNA samples were collected from four different ethnic groups of the Noir Marron population of French Guiana. RHD and RHCE genotyping was performed using DNA microarray and/or sequencing. Results and discussion: Significant allelic diversity was shown, with 45% of individuals presenting an RHD gene variant (most common: RHD*DAU, RHD*DIVa, and RHD*DIIIa allele) and 9.4% with a partial D phenotype. Likewise, 85% presenting an RHCE gene variant and 9% a partial RH2 antigen. One original allele was identified in two D+ Noir Marron individuals: a hybrid RHD*DIIIa‐CE(9)‐D allele, encoding probably a partial D antigen and associated with an RHCE*ce(48C, 733G, 1006T) allele. The African diversity of RHD and RHCE genes is found in this population with preserved genetic but mixed cultural backgrounds. These data allow us to describe the characteristics of the RH system antigen and highlights a significant number of partial antigens with a risk of alloimmunization.